1985
DOI: 10.1902/jop.1985.56.9.548
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Acid Production by Oral Streptococcus mitis Inhibits the Growth of Oral Capnocytophaga

Abstract: Various relationships including inhibition or stimulation of growth have been demonstrated among the bacteria present in dental plaque, both in vitro and in vivo. A large number of these relationships involved oral Streptococci. An earlier study found that strains of Streptococcus mitis inhibited the growth of potential periodontopathic microorganisms, such as Actinobacillus actinomycetemcomitans, Capnocytophaga and species of Bacteroides and Fusobaclerium. The present investigation showed that this inhibitory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Various in vitro and in vivo studies have shown that production of hydrogen peroxide by probiotic bacterial strains can inhibit the growth of pathogenic bacterial species (Mashimo et al 1985, Tompkins & Tagg 1986, Makras & De Vuyst 2006, Falagas et al 2007. In this aspect, Hillman & Shivers (1988) showed in a gnotobiotic rat model that the level of A. actinomycetemcomitans colonization in these rats was 45-fold lower in animals infected with a hydrogen peroxide-producing S. sanguinis strain when compared with rats infected with a hydrogen peroxide-deficient mutant of this S. sanguinis strain.…”
Section: Antimicrobial Substances Produced By Probioticsmentioning
confidence: 99%
“…Various in vitro and in vivo studies have shown that production of hydrogen peroxide by probiotic bacterial strains can inhibit the growth of pathogenic bacterial species (Mashimo et al 1985, Tompkins & Tagg 1986, Makras & De Vuyst 2006, Falagas et al 2007. In this aspect, Hillman & Shivers (1988) showed in a gnotobiotic rat model that the level of A. actinomycetemcomitans colonization in these rats was 45-fold lower in animals infected with a hydrogen peroxide-producing S. sanguinis strain when compared with rats infected with a hydrogen peroxide-deficient mutant of this S. sanguinis strain.…”
Section: Antimicrobial Substances Produced By Probioticsmentioning
confidence: 99%
“…Interactions between mierobial species have been shown to play a significant role for the growth of microorganisms in in vitro studies (5,6,8,14,23,26) and in experitnental infections in laboratory animals (1,4,13,15,19,28,30). In more complex iti vivo systems, such as subgingival plaque, mierobial interactions have beet-i less well studied.…”
mentioning
confidence: 99%
“…The number of different species which reside in this area has been estimated at over 300 (28), Electron microscopy of in situ plaque sections has revealed that the organisms live in densely packed masses (19), Thus, there are continuous opportunities for interactions between species within this niche and between the microorganisms and the host. For a considerable time, investigators have examined associations between microbial species in vitro and laboratory animals, seeking cell surface interactions (18,25,36), antagonisms (1,3,16,17,22,31,41,43,44,47), synergisms or symbiosis (8,9,38,45) and associations which play a role in "mixed infections" (7, 20, 21, 23, 24, 26, 27, 30, 32-34, 37, 40, 41), There have been few studies which have examined microbial associations as they exist in human dental plaque (46,48), One widely studied interaction has been between the suspected pathogen, Actinobacittus actinomycetemcomitans and 3 possibly beneficial species. Streptococ-cus sanguis.…”
mentioning
confidence: 99%